Popular Diets: Ketogenic Diet - Kelsey Gemmill; Daniela Rivero-Mendoza; Wendy J. Dahl (EDIS)
The ketogenic diet is a high-fat, very low carbohydrate diet. The first documented use of the ketogenic diet was in 1921 to treat epilepsy in children. In the past few years, the ketogenic diet has resurged in popularity as a potential means for weight loss. The ketogenic diet has become popular due to celebrity endorsement and social media influences. This new 4-page publication of the UF/IFAS Food Science and Human Nutrition Department explains the concepts behind this diet, explores the available menu, and examines whether this diet is safe and effective. Written by Kelsey Gemmill, Daniela Rivero-Mendoza, and Wendy Dahl. https://edis.ifas.ufl.edu/fs403